Asya krizinin Türk ve dünya ekonomisine etkileri - Özdemir, İsmail (My University, 2000)
The duration of globalisim which started in the 1980's years and particularly increased sharply the effects and forces the beginning of the 1990's years, caused the changes on the method of productions, competition between administratings, finantial market and consequently the governments' , the world's economical, political and cultural movements. Parallel to the changes in the mentioned world economy, a variation became in the world scale investment activity character. The Investment activities which have the finantial function comen out by the international basic unbalanced, went far from that functionality quickly, it chased morely arbitrage gain , turned into speculative status money behaviours. In the globalism term, the volume of the investment activities which changed merely form, enlarged and tended morely the developing countries with respect to the old terms activities. The volume of the tending reached the top point in the middle of the 1990's years. That development which caused the mentioned coutries to have the sources more widely, especially contributed their growing up performance, that's certainly fact. But, investment activities's obtained function and character , in the same period , caused appearing of the important problems. The growing up volume to parallel to the flowing of the investments to the developing countries, the probability of the financial crisis increased as an effect of that economy.After 1980's external debt, the defination of the 1990's years with such as the crisis. The mentioned cases, that's the globalisim which would been thought to prove the positive additions, appeared a case that changed to tern into creating the duration of crisis. In 1990's years , the general characteristics of the many crisises which were created by the globalism, were money crisisis. The latest model of that was Asia Crisis that we have been still feeling. In that thesis, such as the reasons caused the Asia Crisis as a money crisis, its effects on Turkey and the worlds's economy, the prevention of the probable money crisises, reform suggections for managing after the comen out cirisis are taken up.
Keywords: Uluslararası Finans-Asya; Uluslararası Finans-Türkiye